Social work and the making of social policy - Klammer, Ute 1963-; Leitner, Sigrid 1970-; Leiber, Simone ca. 20./21. Jh (Policy Press, 2019)
Bringing together international case studies, this book offers theoretical and empirical insights into the interaction between social work and social policy
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Front cover; Title Page; Copyright Page; Table of Contents; List of figures and tables; Notes on contributors; Acknowledgements; 1. Introduction: social work and the making of social policy; Part I: Social work, problem definition and agenda setting; 2. Social work as policy innovator: challenges and possibilities in the UK; 3. Social work, problem definition and policy change in the US: the case of sex-trafficked youth; 4. The voices of Italian social workers: from a pilot anti-poverty intervention to a national policy; Part II: Social work interests in policy formulation and decision making
5. Social reform in the US: lessons from the Progressive Era6. Social work academia and social policy in Israel: on the role of social work academics in the policy process; 7. Social workers' collective policy practice in times of austerity: Italy and Spain compared; 8. Social policy and welfare movements 'from below': the Social Work Action Network (SWAN) in the UK; Part III: Social work and implementation; 9. Policy work and the ethics of obedience and resistance: perspectives from Britain and beyond; 10. Systemic barriers to effective implementation of child protection reform in Israel
11. Social workers implementing social assistance in Spain: reshaping poverty in a familialistic welfare state12. Layering, social risks and manufactured uncertainties in social work in Poland; 13. 'A little more humanity': placement officers in Germany between social work and social policy; 14. Conclusion: social work and the making of social policy -- lessons learned; Index; Back cover
Keywords: Social service; Social policy; Sozialarbeit; Sozialpolitik; Aufsatzsammlung